2010
DOI: 10.1055/s-0030-1250433
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Pharmacokinetics and Tissue Distribution after Repeated Dosing of the Roots ofScutellaria baicalensisin Rats

Abstract: Scutellariae Radix (root of Scutellaria baicalensis, SR) contains numerous flavonoids such as baicalin, baicalein, and wogonin. This study investigated the pharmacokinetics and tissue distribution of flavonoids and their metabolites in rats after repeated dosing of a SR decoction. Sprague-Dawley rats were orally administered SR at 2 g/kg for seven doses. After the 7th dose, blood samples were withdrawn at specific times and organs, including the liver, kidney, lung, and brain, and collected. The concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…The only free form found in the circulation was rhein, which also presented mainly as its glucuronides/sulfates (Shia et al, 2009). Later, another our study reporting the tissue distribution of flavonoids of Scutellariae Radix (root of Scutellariae baicalensis) disclosed that the free forms of baicalein and wogonin were the major forms in many organs, in contradiction to the finding in blood (Hou et al, 2011). Therefore, in order to elucidate the real molecular forms and concentrations of rhubarb anthraquinones in the circulation and in various organs at the steady state, pharmacokinetic and tissue distribution studies following repeated dosing of RP decoction were conducted in rats.…”
Section: Introductionmentioning
confidence: 74%
“…The only free form found in the circulation was rhein, which also presented mainly as its glucuronides/sulfates (Shia et al, 2009). Later, another our study reporting the tissue distribution of flavonoids of Scutellariae Radix (root of Scutellariae baicalensis) disclosed that the free forms of baicalein and wogonin were the major forms in many organs, in contradiction to the finding in blood (Hou et al, 2011). Therefore, in order to elucidate the real molecular forms and concentrations of rhubarb anthraquinones in the circulation and in various organs at the steady state, pharmacokinetic and tissue distribution studies following repeated dosing of RP decoction were conducted in rats.…”
Section: Introductionmentioning
confidence: 74%
“…Therefore, suppressing inflammatory response could attenuate renal fibrosis. Baicalein (5,6,7-trihydroxyflavone) is a natural flavonoid extracted from the Chinese herb Scutellaria baicalensis (Hou et al 2011). It has been widely used as a therapeutic agent for microbial infection in East Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of pharmacokinetics studies to investigate absorption of BG and B. 811 Akao et al compared in vivo absorption of BG and B in regular rats to that in germ-free rats and suggested that BG underwent intestinal conversion to B, which is absorbed rapidly and converted back to BG in the systemic circulation. 11 An in situ absorption experiment revealed the existence of double-site absorption of BG.…”
mentioning
confidence: 99%